Micropunching Lithography for Generating Micro- and Submicron-patterns on Polymer Substrates - Chakraborty, Anirban (MyJove Corporation, 2012)
Conducting polymers have attracted great attention since the discovery of high conductivity in doped polyacetylene in 1977(1). They offer the advantages of low weight, easy tailoring of properties and a wide spectrum of applications(2,3). Due to sensitivity of conducting polymers to environmental conditions (e.g., air, oxygen, moisture, high temperature and chemical solutions), lithographic techniques present significant technical challenges when working with these materials(4). For example, current photolithographic methods, such as ultra-violet (UV), are unsuitable for patterning the conducting polymers due to the involvement of wet and/or dry etching processes in these methods. In addition, current micro/nanosystems mainly have a planar form(5,6). One layer of structures is built on the top surfaces of another layer of fabricated features. Multiple layers of these structures are stacked together to form numerous devices on a common substrate. The sidewall surfaces of the microstructures have not been used in constructing devices. On the other hand, sidewall patterns could be used, for example, to build 3-D circuits, modify fluidic channels and direct horizontal growth of nanowires and nanotubes. A macropunching method has been applied in the manufacturing industry to create macropatterns in a sheet metal for over a hundred years. Motivated by this approach, we have developed a micropunching lithography method (MPL) to overcome the obstacles of patterning conducting polymers and generating sidewall patterns. Like the macropunching method, the MPL also includes two operations (Fig. 1): (i) cutting; and (ii) drawing. The "cutting" operation was applied to pattern three conducting polymers(4), polypyrrole (PPy), Poly(3,4-ethylenedioxythiophen)-poly(4-styrenesulphonate) (PEDOT) and polyaniline (PANI). It was also employed to create Al microstructures(7). The fabricated microstructures of conducting polymers have been used as humidity(8), chemical(8), and glucose sensors(9). Combined microstructures of Al and conducting polymers have been employed to fabricate capacitors and various heterojunctions(9,10,11). The "cutting" operation was also applied to generate submicron-patterns, such as 100- and 500-nm-wide PPy lines as well as 100-nm-wide Au wires. The "drawing" operation was employed for two applications: (i) produce Au sidewall patterns on high density polyethylene (HDPE) channels which could be used for building 3D microsystems(12,13,14), and (ii) fabricate polydimethylsiloxane (PDMS) micropillars on HDPE substrates to increase the contact angle of the channel(15).